2017
DOI: 10.1186/s13293-016-0123-5
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific differences in hypothalamus–pituitary–adrenal axis activity during childhood: a systematic review and meta-analysis

Abstract: BackgroundGender-specific differences in hypothalamus–pituitary–adrenal (HPA) axis activity have been postulated to emerge during puberty. We conducted a systematic review and meta-analysis to test the hypothesis that gender-specific differences in HPA axis activity are already present in childhood.MethodsFrom inception to January 2016, PubMed and EMBASE.com were searched for studies that assessed non-stimulated cortisol in serum or saliva or cortisol in 24-h urine in healthy males and females aged ≤18 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 53 publications
2
42
0
Order By: Relevance
“…A systematic review recently published by van der Voorn et al has reported that gender differences in HPA axis activity are already present in childhood: in boys aged <8 years higher salivary cortisol levels compared to girls were found and this pattern was reversed after the age of 8 years. However, gender differences in serum cortisol of boys and girls <8 years or 8–18 years were absent [ 15 ]. Moreover, in patients with congenital adrenal hyperplasia the needed dosage of hydrocortisone at puberty seems to be significantly higher in males compared to females [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review recently published by van der Voorn et al has reported that gender differences in HPA axis activity are already present in childhood: in boys aged <8 years higher salivary cortisol levels compared to girls were found and this pattern was reversed after the age of 8 years. However, gender differences in serum cortisol of boys and girls <8 years or 8–18 years were absent [ 15 ]. Moreover, in patients with congenital adrenal hyperplasia the needed dosage of hydrocortisone at puberty seems to be significantly higher in males compared to females [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most parsimonious model was chosen for the purposes of data interpretation. Sex and puberty which - generally starts earlier in girls- influence the cortisol secretion 51 . As puberty status was not assessed in the study, sex, age, age², sex x age, and sex x age² were included as covariates in all models, to allow for different age effects in boys and girls and the fact that these may be curvilinear.…”
Section: Methodsmentioning
confidence: 99%
“…We recently showed that basal HPA axis activity, represented by non-stimulated cortisol concentrations in saliva and free cortisol in 24-h urine, show sexual dimorphism, with a sex-specific change induced by puberty [8]. In addition, gender differences in the reactivity of the HPA axis have also been described in children [4, 9, 10], although evidence is scarce and not systematically reviewed.…”
Section: Introductionmentioning
confidence: 99%